The THE EFFECTS OF LOCAL CULTURE ON TOURISM PRODUCTS AND DOMESTIC TOURIST SATISFACTION IN TOURISM DESTINATIONS : IN GIANYAR REGENCY, IN THE PROVINCE OF BALI - Bagus, Cempena; BrahmaSari, Ida Aju; Suryani, Tatik (Archives of Business Research, 2020)
The beauty of nature, the uniqueness of the culture and the hospitality of its inhabitants put the island of Bali first in the world, beating the Maldives and Phuket, Thailand. Bali ranks first among the 25 best destinations in the world (Trip Adivisor, 2017). The purpose of this study is to prove and analyze the influence of local culture on tourism products and the satisfaction of domestic tourists at tourist destinations in Gianyar regency of Bali province. The population in this study is domestic tourists whose numbers are unknown (unlimited). Convenience sampling was used of 204 respondents. The results of this study prove that local culture has a significant influence on tourism products and the satisfaction of the domestic tourists, as well as the tourism products have a significant effect on the satisfaction of the domestic tourists Keywords: local culture, tourism products, tourist satisfaction.